Analisis Tingkat Kepuasan Petani Terhadap Layanan Penyuluhan Pertanian di Kecamatan Larompong - Bahtiar Bahtiar; Dewi Marwati Nuryanti; Akmal Akmal (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2024)
This research will be conducted in all sub-districts in Larompong District, namely 13 sub-districts. The results of the study indicate that the level of satisfaction of rice farmers with the quality of agricultural extension services in Larompong District, Luwu Regency is in the satisfied category based on 15 attributes of questions answered by respondent farmers where the attribute with the highest level of farmer satisfaction is that extension workers conduct field visits to meet or attend meetings with farmers and farmer groups. The level of interest and performance towards agricultural extension services in Larompong District, Luwu Regency based on the analysis of Performance and Information In general, it shows that the level of performance of agricultural extension workers in Larompong District, Luwu Regency is satisfactory. Furthermore, from the results of the calculation of the gap between interests and performance, the gap in each service attribute is positive with a difference between performance and interests of 1.10 out of 5.0. This means that the satisfaction felt by farmers is greater than the performance of extension workers towards the interests of farmers. Based on the results of multiple linear regression, the independent variables that have a significant effect on the dependent variable are the variables Age, Education and Experience on the level of farmer satisfaction with extension services.